2016
DOI: 10.17323/1814-9545-2016-1-61-83
|View full text |Cite
|
Sign up to set email alerts
|

Do Anti-Corruption Educational Campaigns Reach Students? Some Evidence from Russia and Ukraine

Abstract: Abstract. The authors investigate the effect of anti-corruption educational materials -an informational folder with materials designed by Transparency International -on the willingness of students to participate in an anti-corruption campaign and their general judgment about corruption in two cities in Russia and Ukraine by conducting experiments. During a survey of 350 students in Khabarovsk, Russia, and 600 students in Lviv, Ukraine, young people were randomly exposed to either a folder with information abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 9 publications
(9 reference statements)
2
9
0
Order By: Relevance
“…Some scholars often do not dare to call it "corruption" and mitigate this small "sin" by referring to it as "student dishonesty", "academic dishonesty", "cheating", or just simply "plagiarism" (s. e.g. Curtis et al 2013;Golunov 2014;Curtis and Vardanega 2016;Chapman and Linder 2016;Denisova-Schmidt 2016a;Denisova-Schmidt et al 2016a). The challenges of defining "corruption" might also be explained by the fact that corruption is a crime.…”
Section: Corruption Research As a Field Of Studymentioning
confidence: 99%
“…Some scholars often do not dare to call it "corruption" and mitigate this small "sin" by referring to it as "student dishonesty", "academic dishonesty", "cheating", or just simply "plagiarism" (s. e.g. Curtis et al 2013;Golunov 2014;Curtis and Vardanega 2016;Chapman and Linder 2016;Denisova-Schmidt 2016a;Denisova-Schmidt et al 2016a). The challenges of defining "corruption" might also be explained by the fact that corruption is a crime.…”
Section: Corruption Research As a Field Of Studymentioning
confidence: 99%
“…An assumption is often made that corrupt exchanges are driven by academics, and the students are victimised as a result. Evidence suggests that the initiators of bribes may be lecturers, either indirectly or directly (Denisova-Schmidt, Huber and Leontyeva, 2016a). In many instances, however, the initiators of misconduct in general and bribes more specifically are the students themselves.…”
Section: What Is Academic Corruption and What Drives Students To Engamentioning
confidence: 99%
“…Perceptions of the issue: Previous research has shown that people who believe that everyone around them is corrupt are more prone to corruption and cheating (John, Loewenstein, Rick, 2014;Corbacho et al 2016, Denisova-Schmidt, Huber Prytula, 2015and Denisova-Schmidt, Huber and Leontyeva, 2016a. A study by Shaw, Katsaiti and Pecoraro (2015) found that perceptions of the corruption of others has had a positive impact on personal involvement of students in Ukraine.…”
Section: Independent Variables and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Corbacho et al (2016) find for an information experiment in Costa Rica that individuals who believe that everyone around them is corrupt and/or who have personal experience with corruption are more prone to corruption. Finally, our paper is related to Denisova-Schmidt et al (2015) and Denisova-Schmidt et al (2016), which investigate the effectiveness of an anti-corruption folder developed by Transparency International among students in Lviv, Ukraine and Khabarovsk, Russia, respectively. We improve upon these previous studies by considering more and different interventions (both brochures and videos), using a larger sample, and more thoroughly investigating effect heterogeneity.…”
mentioning
confidence: 99%